Investment Promotion Planning: The Case Of Mandalika Resort, Lombok - Dicky Arsyul Salam; Beta Budisetyorini (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2018)
This research aimed to provide a best practice, generalizable model, of investment promotion planning for use by tourism IPA in Mandalika Resort, which is needs a huge amount of investments for its development. In the research methodology chapter, this research employed subjectivist with inductive approach, along with case study strategy. Data were collected by utilizing a semi-structured interview. The data collected were analyzed by using a triangulation, thus this research was adopted the qualitative method. The data collected was analysed, and the findings shows that there are a lot of spot for improvement in all the area of investment promotion that been manage by BKPM. The current practice by BKPM as the national IPA is not enough to obtain all the investment needs of Mandalika Project. As the recommendation, this research proposes to create a new form of IPA, that manage specifically the tourism sector in Indonesia.